2020
DOI: 10.1111/fcp.12597
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of fenofibrate against high‐fat–high‐fructose diet induced non‐obese NAFLD in rats

Abstract: The present study evaluated the protective effects of fenofibrate on liver function, oxidant–antioxidant balance, and insulin resistance (IR) in rats fed high‐fat–high‐fructose diet (HFFD). Twenty‐four male Sprague‐Dawley rats (110–130 gm) were allocated into four equal groups (n = 6). Rats in group I were fed a normal diet for 4 weeks. Rats in group II were fed a normal diet with fenofibrate at 50 mg/kg/day orally for four weeks. Rats in group III were fed a normal diet mixed with 25% palm oil and given 60% f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 50 publications
3
7
0
Order By: Relevance
“…This synthesizes TG and very low-density lipoprotein and produces secretions [15]. Another report showed that fenofibrate increases levels of high-density lipoprotein by inducing the expression of Apo A1 and A2 [16], and its effectiveness against fatty liver has been demonstrated [17]. It is speculated that the body weight and liver weight reduction tendencies in the present study are caused by the accentuation of the fatty acid oxidation differentiation process due to the Pparα activation action of fenofibrate.…”
Section: Discussionsupporting
confidence: 49%
“…This synthesizes TG and very low-density lipoprotein and produces secretions [15]. Another report showed that fenofibrate increases levels of high-density lipoprotein by inducing the expression of Apo A1 and A2 [16], and its effectiveness against fatty liver has been demonstrated [17]. It is speculated that the body weight and liver weight reduction tendencies in the present study are caused by the accentuation of the fatty acid oxidation differentiation process due to the Pparα activation action of fenofibrate.…”
Section: Discussionsupporting
confidence: 49%
“…Restriction of calorie intake when supplying high fructose failed to induce obesity but still triggered steatosis in rats ( Roncal-Jimenez et al, 2011 ). Even supplement with high palm oil in high fructose diet, the rats tend to become non-obese NAFLD model ( Abdelmoneim et al, 2021 ), suggested fructose induction may account for lean NAFLD. Lean NAFLD makes up about one-third of the NAFLD population, according to recent studies, lean NAFLD may potentiate higher metabolic risks than obese NAFLD.…”
Section: Discussionmentioning
confidence: 99%
“…[53] Furthermore, fenofibrate-activated PPARα improves various stages of NAFLD by promoting fatty acid metabolism and inhibiting pro-inflammatory reactions. [54] In addition, fenofibrate improves hepatic vascular status by induction of catalase (CAT) expression and depression of the levels of hepatic H 2 O 2 levels [55] and cyclooxygenase-1 (COX-1). [56] Furthermore, fenofibrate has been reported to suppress the decrease in hepatic PPARα expression with the progression of liver fibrosis in NASH patients.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of PPARα promotes β‐oxidation in peroxisomes and mitochondria, increases hepatic lipid turnover, and as the results, it down‐regulates hepatic lipid accumulation, inflammation, and fibrosis [53] . Furthermore, fenofibrate‐activated PPARα improves various stages of NAFLD by promoting fatty acid metabolism and inhibiting pro‐inflammatory reactions [54] . In addition, fenofibrate improves hepatic vascular status by induction of catalase (CAT) expression and depression of the levels of hepatic H 2 O 2 levels [55] and cyclooxygenase‐1 (COX‐1) [56] .…”
Section: Discussionmentioning
confidence: 99%